1989
DOI: 10.1115/1.3250728
|View full text |Cite
|
Sign up to set email alerts
|

Flow and Heat Transfer in the Space Between Two Corotating Disks in an Axisymmetric Enclosure

Abstract: A numerical investigation was undertaken to characterize the laminar flow and heat transfer in axisymmetric coaxial corotating shrouded disk configurations. Attention was focused on calculation conditions favoring steady, stable, symmetric solutions of the conservation equations. The justification for this is based on velocity measurements obtained in a test section that matches the numerical configuration. Calculations were performed to investigate the dependence of the flow characteristics on disk angular ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…1. Cross-stream vector velocity field (compressed in radial direction) [5]. average A relative to r observed that the inner region boundary was oval in a plane parallel to the fins when the separation distance between the edge of the fins and the shroud approached infinity.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…1. Cross-stream vector velocity field (compressed in radial direction) [5]. average A relative to r observed that the inner region boundary was oval in a plane parallel to the fins when the separation distance between the edge of the fins and the shroud approached infinity.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Abrahamson [4], Chang [5], Humphrey [6] and Herrero [7] have studied flow characteristics in an enclosed co-rotating disk pair (ECDP), which is an idealization of an unobstructed computer disk storage system. Schuler et al [8], Tzeng [9], Gor [10] and Cho [11] have investigated flow structures and heat/mass transfers between shrouded co-rotating disks (i.e., equivalent to an ECDP), with and without an obstruction (i.e., the head arm) and with and without a ventilation flow through the hub.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the contour plots, solid lines represent positive values of the variable and dashed lines represent negative values. In the streamline plot, a clockwise flow recirculation is represented by negative values of the streamfunction, defined in Equation (9).…”
Section: Aspect Ratio Y =0186mentioning
confidence: 99%
“…Other numerical investigations of unobstructed flows between co-rotating disks in cylindrical enclosures include the axisymmetric steady flow cases investigated by Chang et al [9] and Tzeng and Fromm [10] in the laminar regime, and by Chang et al [11] and Tzeng and Humphrey [5] in the turbulent regime. However, the most interesting numerical results correspond to the two-and three-dimensional unsteady flow cases calculated by Humphrey et al [6] for the experimental conditions investigated by Schuler et al [4].…”
mentioning
confidence: 99%
“…Flow visualization techniques (Lennemann et al, 1974;Abrahamson et al, 1989;Humphrey and Gor, 1993) or point-wise velocity measurements (Chang et al, 1989;Schuler et al, 1990;Chen, 2002, 2003;Wu et al, 2006;Wu, 2009) were applied in early experimental studies. However, a complete experiment conducted in both the r   plane and the rz  plane was still not found.…”
mentioning
confidence: 99%